2000
DOI: 10.1111/j.1365-2613.2000.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

GB Virus C/Hepatitis G Virus (GBV‐C/HGV): still looking for a disease

Abstract: GB Virus C and Hepatitis G Virus (GBV-C/HGV) are positive, single-stranded flaviviruses. GBV-C and HGV are independent isolates of the same virus. Transmission via the blood-borne route is the commonest mode, although vertical and sexual transmission is well documented. GBV-C/HGV is distributed globally; its prevalence in the general population is 10 fold higher in African countries than in non-African countries. High prevalences of GBV-C/HGV have been found in subjects with frequent parenteral exposure and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 208 publications
(328 reference statements)
1
4
0
1
Order By: Relevance
“…The overall prevalence of GBV‐C viremia has been shown to be higher among high‐risk groups with parenteral exposures, for example, PWID and haemodialysis patients, compared to blood donors [Sathar et al, ; Christensen et al, ; Reshetnyak et al, ]. Our study found GBV‐C viremia in Estonia to be 33% and 6% among PWIDs and healthy volunteers, respectively.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The overall prevalence of GBV‐C viremia has been shown to be higher among high‐risk groups with parenteral exposures, for example, PWID and haemodialysis patients, compared to blood donors [Sathar et al, ; Christensen et al, ; Reshetnyak et al, ]. Our study found GBV‐C viremia in Estonia to be 33% and 6% among PWIDs and healthy volunteers, respectively.…”
Section: Discussionsupporting
confidence: 48%
“…The prevalence of GBV‐C viremia in general populations varies, being lower (1–5%) in developed countries and higher (up to 20%) in developing countries [Wachtler et al, ; Reshetnyak et al, ; Mohr and Stapleton, ]. However, in individuals with various underlying conditions, for example, HIV positive (HIV+) persons, patients receiving haemodialysis, people who inject drugs (PWID), the occurrence of GBV‐C viremia up to 45% has been reported [Rey et al, ; Sathar et al, ; Reshetnyak et al, ]. GBV‐C viremia is particularly of interest in the context of HIV‐1 and GBV‐C co‐infection.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that serum samples that are positive for the antibodies are negative for viral RNA and vice versa which makes HPgV anti-E2 a marker for resolved infection. 35 HPgV anti-E2 was detected in 6 of 15 liver transplant patients, 5 of 15 children with decompensated liver disease and 1 of 20 controls (Table 2). This indicates that there was previous HPgV infection in the HPgV anti-E2 positive children.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, multiple GBV-C genotypes that display a propensity to recombine may infect the same person (Slavov et al, 2019;dos Santos Bezerra et al, 2020). Vertical, parental and sexual transmission of GBV-C have been reported (Sathar et al, 2000). The frequency and occurrence of the GBV-C infection are higher in risk groups that are vulnerable to sexually transmitted or blood-borne infections (Scallan et al, 1998;Christensen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%